Recent occurrences and regulation enforcement of per- and polyfluorinated substances in drinking water - Nurlin, Abu Samah (Institut Kimia Malaysia, 2024)
Per- and polyfluorinated substances (PFAS) have emerged as significant contaminants in drinking water sources, garnering widespread attention due to their persistence, toxicity, and potential health risks. This article provides a comprehensive overview of recent occurrences of PFAS in drinking water and the regulatory measures enforced to mitigate their impact. It synthesizes current research findings, highlighting the prevalence of PFAS contamination across various regions and its implications for public health. Additionally, it examines the regulatory landscape governing PFAS, including legislative initiatives and enforcement actions aimed at monitoring and controlling these contaminants. By analysing the intersection of scientific research and regulatory efforts, this abstract offers insights into the ongoing challenges and advancements in addressing PFAS contamination in drinking water.